2000
DOI: 10.4049/jimmunol.164.3.1625
|View full text |Cite
|
Sign up to set email alerts
|

Linear PADRE T Helper Epitope and Carbohydrate B Cell Epitope Conjugates Induce Specific High Titer IgG Antibody Responses

Abstract: Linear carbohydrate-peptide constructs based on the 13 amino acid nonnatural pan DR epitope (PADRE) and carbohydrate B cell epitopes are demonstrated to be potent immunogens. These data support our belief that PADRE should be considered as an alternative to more complex carriers for use in prophylaxis and therapeutic vaccines. Two model carbohydrate-PADRE glycoconjugates were used to demonstrate that PADRE could effectively provide T cell help for carbohydrate-specific Ab responses. Conjugates of PADRE covalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(147 citation statements)
references
References 49 publications
3
135
0
Order By: Relevance
“…Finally, we investigated the effect of P 3 CSK 4 on CD4 + T cell responses to two HLA-DR-promiscuous, immunodominant epitopes derived from two common human pathogens: TT 947-967 and hepatitis B surface antigen (HBsAg) [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] [23,24]. A higher frequency of peptidespecific T cells in cultures conditioned by P 3 CSK 4 as compared to CSK 4 was demonstrated by LDA analysis (Fig.…”
Section: Blpa Bearing At Least Two Ester-bonded Palmitoylated Side Chmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we investigated the effect of P 3 CSK 4 on CD4 + T cell responses to two HLA-DR-promiscuous, immunodominant epitopes derived from two common human pathogens: TT 947-967 and hepatitis B surface antigen (HBsAg) [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] [23,24]. A higher frequency of peptidespecific T cells in cultures conditioned by P 3 CSK 4 as compared to CSK 4 was demonstrated by LDA analysis (Fig.…”
Section: Blpa Bearing At Least Two Ester-bonded Palmitoylated Side Chmentioning
confidence: 99%
“…TT, TT 947-967 and HBsAg [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] peptides, and rIL-2 were provided by Dr. A. Wack (Chiron Vaccines, Siena, Italy). GM-CSF was from R&D Systems (Abingdon, UK).…”
Section: Chemicals Antigens Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in the experiments cited above by Bhardwaj and colleagues (9), the injection of ex vivo-generated mature dendritic cells obviated the need for helper antigen. A number of preclinical vaccine studies using peptides, proteins, or antigen-pulsed dendritic cells have employed nonspecific Th sequences to stimulate Th cells and to promote an augmented antibody or CTL response (12)(13)(14). Clinical studies with peptide vaccines have not confirmed that nonspecific helper peptides boost CTL immunity (15), but several recent studies indicate that nonspecific helper sequences pulsed onto dendritic cells generate strong Th activity (14,16).…”
Section: Dendritic Cells and Other Adjuvantsmentioning
confidence: 99%
“…In addition, foreign carrier proteins such as keyhole limpet hemocyanin (KLH) and bovine serum albumin (BSA) and the linker that attach the saccharides to the carrier protein can elicit strong B-cell responses, which may lead to the suppression of antibody responses against the carbohydrate epitope 5,6 . It is clear that the successful development of carbohydrate-based cancer vaccines requires novel strategies for the more efficient presentation of tumor-associated carbohydrate epitopes to the immune system, resulting in a more efficient class switch to IgG antibodies [7][8][9][10][11][12][13][14][15][16][17] .…”
mentioning
confidence: 99%